Network Virtualization Incorporation and Projection System Technologies Using Block Chaining. Issue 4 (July 2021) - Prasanna Srinivasan, V; Viswanathan, C; Sailaja, P; Manimala, G
Abstract: With the proposed time-lock encryption method, mutually untrustworthy users will create a shared public key for the implementation in a completely distributed and asyncratic setting like internet or blockchain networks with time-critical privacy conservation applications such as e-voting or online auction. A "putting puzzles inside another puzzle" construction mechanism was proposed to resolve the probabilistic characteristics of the predicted key crack time. Experimental findings indicate that the solution proposed will deliver a more precise main break time, which would make it faster and more exact to reach the expected time limit. As described above, we can further estimate computing power by combining our scheme and the blockchain, to decode time-sensitive message. Miners are ready to supply under the updated PoW scheme.